Measurement of D⁎±, D± and D±s meson production cross sections in pp collisions at √s = 7 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Davygora, Yuriy; Djuvsland, Julia Isabell; Dunford, Monica; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (Nuclear physics. B, Particle physics, 2016)
The production of D⁎±, D± and Ds± charmed mesons has been measured with the ATLAS detector in pp collisions at s=7 TeV at the LHC, using data corresponding to an integrated luminosity of 280 nb−1. The charmed mesons have been reconstructed in the range of transverse momentum 3.5<pT(D)<100 GeV and pseudorapidity |η(D)|<2.1. The differential cross sections as a function of transverse momentum and pseudorapidity were measured for D⁎± and D± production. The next-to-leading-order QCD predictions are consistent with the data in the visible kinematic region within the large theoretical uncertainties. Using the visible D cross sections and an extrapolation to the full kinematic phase space, the strangeness-suppression factor in charm fragmentation, the fraction of charged non-strange D mesons produced in a vector state, and the total cross section of charm production at s=7 TeV were derived.
*ATLAS Collaboration: G. Aad, C.F. Anders, V. Andrei, A.E. Baas, O. Brandt, Y. Davygora, J.I. Djuvsland, M. Dunford, M.P. Geisler, M. Giulini, P. Hanke. J. Jongmanns, E.-E. Kluge, M. Kretz, A. Kugel, V.S. Lang, M. Lisovyi, K. Meier, S. Schaetzel, V. Scharf, S. Schmitt, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, R. Stamen, M. Wessels [und 2812 weitere Personen]
Im Titel sind die Zeichen "⁎", "+" und "-" hochgestellt
Im Titel ist Buchstabe s in der Formulierung D±s tiefgestellt
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 25.06.2020